NURSES IMAGE AS SEXUAL OBJECT IN THE MEDIA: A PROFESSIONAL HARASSMENT - Julio Cesar Colpo; Vania Carla Camargo; Simey Ariane Mattos (Universidade Federal do Paraná, 2006)
Media, specially the Internet, convey information that explores nurses body as a sexual object, harming their image. Some factors contribute for the definition of nursing negative stereotype: its historical past (having been exercised by socially stigmatized women such as prostitutes, alcoholic, illiterates); sexual work division; its background based on medical knowing. Concomitant to the historical accounts, in search sites, if you enter nurse, you can find many files with many erotic illustrations (figures, photos, drawings, among others) that stimulate popular imagination and expose nursing professionals to embarrassing situations. On the other hand, when you enter male nurse, it is seriously addressed. This article confirms the existence of sexist prejudice against Nursing, and points out confrontation strategies to the problem as well as taunting the true image, thus granting the professionals with the social recognition they deserve for their responsibility, performance and significance to global society.